Gas phase glycerol dehydration to acrolein over supported silicotungstic acid catalyst - Kiakalaieh, Amin Talebian (2015)
Due to the various environmental concerns, a steep hike in fossil fuel price and an increasing demand of non-renewable fossil fuels consumption, the bio-basedgas-phase dehydration of glycerol to acrolein has attracted much attention recently.Thus, the gas phase dehydration of glycerol to acrolein over two groups of supported silicotungstic acid on aluminum oxide (Al2O3) nanoparticle and zirconium dioxide catalyst is being investigated in this study. The catalysts were characterized by, Xraydiffraction, Fourier transform infrared spectroscopy, field-emission scanning electron microscopy and energy dispersive X-ray techniques, temperature programmed desorption, thermogravimetric analysis, and elemental analyzer. The characterization results revealed that Al2O3 nano particle loading increased thermal stability, pore diameter, and specific surface area of the synthesized catalysts.Optimization by response surface methodology revealed the highest acrolein selectivity of 88.5% at 97% glycerol conversion was obtained over 30HZ-20Acatalyst with turnover frequency being 136 h-1 in 3 h for glycerol feed concentration of 10.3 wt% and 0.5 g catalyst at 300 ˚C. Coke deposition has no significant effect on the catalyst activity due to the large catalyst pore diameter (> 27 nm). The prepared catalysts were highly active and selective for acrolein production even after 40 h without any needs for gas co-feeding or application of noble metals. In addition, the kinetic study results demonstrated that glycerol dehydration to acrolein followed first-order rate with the activation energy (Ea) of 27.5 kJ/mol and frequency factor(A) of 5.35×105 s-1. Finally, the theoretical and experimental approaches confirmed no internal mass transfer limitation in glycerol dehydration reaction with catalyst pellet sizes of dp= 2-4 and 5-7 μm due to effectiveness factor equal to 1 (η=1).Calculation of the overall effectiveness factor (Ω) also confirmed the absence of external diffusion in presence of catalysts with pellet size of dp< 7 μm